Energy management control strategies for energy storage systems of hybrid electric vehicle: A review - Veerendra Babu, Arigela Sri Satya; Mohd Rusllim, Mohamed; Garcia Marquez, Fausto Pedro (John Wiley and Sons Inc, 2024)
Continuous efforts to preserve the environment and to reduce gaseous emissions due to the massive growth of urban economic development and heightened concerns over crude oil depletion have accelerated researchers to find long-term solutions, particularly in the transportation sector with the focus on powertrain electrification. This article delivers a comprehensive overview of electric vehicle architectures, energy storage systems, and motor traction power. Subsequently, it emphasizes different charge equalization methodologies of the energy storage system. This work's contribution can be identified in two points: first, providing an overview of different energy management methods to researchers and scholars. Second, to highlight the state-of-the-art leanings in major components and to highlight promising approaches to hybrid electric vehicle future development.